Alternative High-Plasma Beta Regimes of Electron Heat-Flux Instabilities in the Solar Wind - Lopez-Escobar, R (IOP Publishing Ltd, 2020)
Heat transport in the solar wind is dominated by suprathermal electron populations, i.e., a tenuous halo and a field-aligned beam/strahl, with high energies and antisunward drifts along the magnetic field. Their evolution may offer plausible explanations for the rapid decrease of the heat flux with the solar wind expansion, and self-generated instabilities, or so-called "heat flux instabilities"(HFIs), are typically invoked to explain this evolution. This Letter provides a unified description of the full spectrum of HFIs, as prescribed by the linear kinetic theory for high beta conditions (β e ≫ 0.1) and different relative drifts (U) of the suprathermals. HFIs of different natures are examined, i.e., electromagnetic, electrostatic or hybrid, propagating parallel or obliquely to the magnetic field, etc., as well as their regimes of interplay (co-existence) or dominance. These alternative regimes of HFIs complement each other and may be characteristic of different relative drifts of suprathermal electrons and various conditions in the solar wind, e.g., in the slow or fast winds, streaming interaction regions, and interplanetary shocks. Moreover, these results strongly suggest that heat flux regulation may not involve just one but several HFIs, concomitantly or successively in time. Conditions for a single, well-defined instability with major effects on the suprathermal electrons and, implicitly, the heat flux, seem to be very limited. Whistler HFIs are more likely to occur but only for minor drifts (as also reported by recent observations), which may explain a modest implication in their regulation, shown already in quasilinear studies and numerical simulations. © 2020. The American Astronomical Society. All rights reserved.